2003
DOI: 10.1079/phn2002427
|View full text |Cite
|
Sign up to set email alerts
|

Addressing overreporting on the International Physical Activity Questionnaire (IPAQ) telephone survey with a population sample

Abstract: Objective: To examine a possible problem of overreporting and to describe the degree of error with the International Physical Activity Questionnaire (IPAQ) short telephone protocol. Design: Cross-sectional study, using two different physical activity (PA) self-report protocols. Setting: Telephone interviews about PA in Belgium. Subjects: Fifty adults who had previously been interviewed with IPAQ in a national survey. Results: Seventy-five per cent reported less PA with the modified procedure than with the IPAQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
316
6
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(347 citation statements)
references
References 11 publications
15
316
6
10
Order By: Relevance
“…The smallest discrepancy reported was an under-estimate by the IPAQ-SF of 28 percent, yet most of these studies reported an over-estimate by the IPAQ-SF and showed considerable variability and the overall mean over-estimate in these studies was 106 percent. Over-reporting of physical activity by the IPAQ-SF is not uncommon [50], and it remains a key limitation of most self-reported measures of physical activity [51]. …”
Section: Discussionmentioning
confidence: 99%
“…The smallest discrepancy reported was an under-estimate by the IPAQ-SF of 28 percent, yet most of these studies reported an over-estimate by the IPAQ-SF and showed considerable variability and the overall mean over-estimate in these studies was 106 percent. Over-reporting of physical activity by the IPAQ-SF is not uncommon [50], and it remains a key limitation of most self-reported measures of physical activity [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Most studies indicate over-reporting of EE 15 . However, in a study with a high degree of overreporting, it was not possible to identify any common characteristics of the individuals who over-report 16 . Misreporting of EE could be due to misreporting of frequency, intensity or duration of activity; however, this has not been much studied.…”
mentioning
confidence: 99%
“…However, accurate and reliable measurement of dietary intake and physical activity at the population level is challenging, particularly in developing countries (2,3) . Various techniques, employing questionnaires, records or objective measurements, have been applied for the assessment of dietary intake and physical activity.…”
Section: Dietary Energy Intake Total Energy Expenditurementioning
confidence: 99%
“…Thus, estimates of PAL, obtained through a physical activity questionnaire, may be used to evaluate the validity of reported energy intake in the same subject and to identify subjects with a tendency to under-report energy intake (13) . On the other hand, some studies have indicated that self-reported instruments have a tendency towards over-reporting of physical activity (2,15) owing to the influence of social desirability and social approval (16) .Methods of assessing energy intake and expenditure have been widely studied in the developed world (17,18) …”
mentioning
confidence: 99%
See 1 more Smart Citation